2010
DOI: 10.4321/s0211-95362010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Milk, social acceptance of a new food in Europe: Catalonia, 19th-20th centuries

Abstract: In this article we analyse the time course of the consumption of fresh milk in different regions of Europe between the 1870s and 1930s. Working from the case of Catalonia, we affirm that the increasing consumption of milk in that period must be especially linked to the spreading of new scientific knowledge in microbiology and nutrition that followed Pasteur's discoveries. We particularly highlight the information dissemination activities in this direction carried out by health sector professionals (medical doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Con todo, había grandes diferencias entre unas y otras ciudades porque grandes eran también las diferencias entre unas y otras regiones: en la España húmeda, con unas condiciones ambientales relativamente propicias para la producción de leche de vaca (y, por tanto, con precios relativos bajos y facilidades para el autoconsumo), la leche estaba mucho más presente en la dieta de la población que en las regiones del interior, el litoral mediterráneo o el sur (Hernández Adell, 2012, cap. 4;Hernández Adell et al, 2013;Nicolau y Pujol, 2006;Muñoz Pradas, 2011;Nicolau et al, 2010;Pujol et al, 2007).…”
Section: Estado De La Cuestiónunclassified
“…Con todo, había grandes diferencias entre unas y otras ciudades porque grandes eran también las diferencias entre unas y otras regiones: en la España húmeda, con unas condiciones ambientales relativamente propicias para la producción de leche de vaca (y, por tanto, con precios relativos bajos y facilidades para el autoconsumo), la leche estaba mucho más presente en la dieta de la población que en las regiones del interior, el litoral mediterráneo o el sur (Hernández Adell, 2012, cap. 4;Hernández Adell et al, 2013;Nicolau y Pujol, 2006;Muñoz Pradas, 2011;Nicolau et al, 2010;Pujol et al, 2007).…”
Section: Estado De La Cuestiónunclassified
“…The information provided by late 19th-and early 20th-century medical-sanitary surveys is illustrative concerning the small number of consumers, as are the reports on the stock-breeding sector in 1891, and the more disperse data on family budgets (Ballesteros, 1997;Pujol-Andreu and Cussó, 2014). Previous research also shows that milk consumption became widespread first among children and young people (Cussó and Garrabou, 2004;Nicolau et al, 2010;Muñoz Pradas, 2016;Nicolau et al, 2010), and that differences according to income in this group were substantial (Carrasco Cadenas, 1934). Finally, other studies have shown that the increase in the availability of milk in those years chiefly affected the stockbreeding northern areas and some big cities (Langreo, 1995;Domínguez Martín, 1996, 2001Hernández and Pujol-Andreu, 2016), and that milk relative prices in the north were lower (Nicolau and Pujol-Andreu, 2006).…”
Section: Conclusion Discussion and Interpretation Of Resultsmentioning
confidence: 90%
“…But, contrary to other major products, milk was not rationed, and there was no systematic milk price policy either nor were there subsidies to farmers or quality‐oriented policies restricting competition in dairy farming, processing, or retailing. Finally, even though physicians and local officers had been spreading the message that milk consumption was good for the health since the late 19th century (Nicolau, Pujol, & Hernández, ), the state was not involved in systematic, centralized propaganda efforts.…”
Section: The Rise and The Fall Of Organized Dairy Capitalismmentioning
confidence: 99%